Peningkatkan Hasil Belajar Matematika Materi Sudut Melalui Model Problem Based Learning Berbantuan Media Jam Sudut Pada Peserta Didik Kelas III SD 2 Mijen - Lestari, Lusiana Indah; Fajrie, Nur; Indriani, Silvia (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve the mathematics learning outcomes of grade III students of SD 2 Mijen on the topic of angles through the implementation of the Problem Based Learning (PBL) model assisted by the Corner Clock media. The method used is the Classroom Action Research (CAR) model of Kemmis and McTaggart, which is carried out in two cycles, each consisting of two meetings. The subjects of the study were 12 students in the even semester of the 2024/2025 academic year. Data collection techniques include observation, testing, and documentation, with instruments in the form of observation sheets and test questions. Data analysis was carried out descriptively quantitatively with reference to individual and classical learning completeness. The results showed that in the pre-cycle, the average student score was 45.4 with a classical completeness of 25%. After the PBL model assisted by the Corner Clock media was implemented, there was an increase in cycle I to 59.2 with a classical completeness of 41.7%, and a significant increase in cycle II with an average score of 77.5 and a classical completeness of 75%. Thus, the implementation of the PBL model assisted by the Corner Clock media has proven effective in improving students' mathematics learning outcomes on the material of angles.